Circular seating arrangements: Approaching the social crux in language classrooms - Falout, Joseph (Studies in Second Language Learning and Teaching, 2014)
Circular seating arrangements can help instill a sense of belonging within classroom communities with overall positive effects on learning, emotions, and wellbeing. Yet students and their teachers within certain language classroom contexts, due to sociocultural limitations, may be relegated to learning in antisocial environments instilled partly by rank-and-file seating. Attributions for teacher demotivation can often lie in student misbehaviors, while student demotivation, silence, and resistance relate strongly to lack of bodily displays and physical affordances of interpersonal care, understanding, and trust that, if present, would contribute positively to many social aspects of their learning and identity formation. Specifically, rank-and-file seating constricts the area in the classroom most likely to dispose attention and interest to the learning and to others, whereas circular seating potentially expands this area, known as the action zone, to the whole classroom. Seating arrangements therefore can play an important role in the formation of interpersonal dynamics and identity formation among students and their teachers. In this paper, the purposes and ways of using circular seating in language classrooms will be explored from a social psychological perspective. Language teachers are invited to imagine and experiment with possibilities for uses of different seating arrangements in their own classrooms.